"It's important, but I'm not going to keep doing it!": Perceived purposes, learning outcomes, and value of pre-service teacher research among educators and pre-service teachers. (November 2019) - van Katwijk, Lidewij; Berry, Amanda; Jansen, Ellen; van Veen, Klaas
Abstract: Attention to the role of pre-service teacher research in teacher education is growing worldwide. This study compares the perceptions of teacher educators and pre-service teachers about the purposes, learning outcomes, and value of pre-service teacher research in different contexts. Questionnaires and interview data from participants in the Netherlands and Australia, identify an inquiry habit of mind as the most important, valuable outcome of pre-service teacher research. Although pre-service teachers consider research frustrating and stressful, they also acknowledge its value as a communication tool and contributor to teacher identity. Yet few of them expect to conduct research in their future jobs. Highlights: Both educators and pre-service teachers consider pre-service teacher research important. An inquiry habit of mind emerges as the most important purpose. Perceived learning outcomes match purposes, namely, to be open-minded, critical, and able to conduct research. Professional development and empowerment are perceived values. Pre-service teachers do not intend to conduct research in their future jobs as teachers.